Women in the International Film Industry: Policy, Practice and Power - Liddy, Susan (Springer International Publishing, 2020)
Keywords: Irina

Gendered Barriers In The Gaming Industry - Singh, Tanya (Journal of Sports Law, Policy and Governance, 2020)
As of 2019, there are an estimated 2.5 billion garners globally. Roughly half of all garners are female. Despite the figures, there is a serious underrepresentation of female gainers in the professional gaming and game development community. It is thus important to examine the underlying causes hindering equally capable female gainers and game developers from pursuing a serious career in gaming, at par with their male counterparts.In this article, the authorexamines the impact of the culturalassociationof games with the male demography, stereotypes andstructuralbarrierslimiting women from realizing theirfullpotential, female representation in video games and workplace, pervasive misogyny and sexual harassment of women across all levels in the industry, and lastly, the steps that can be taken to better the status quo in favour of women.
Keywords: Bibliographie; Irina; Nettoyer

Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion - Cole, Alayna; Zammit, Jessica (CRC Press, 2020)
Description Cooperative Gaming provides context and practical advice regarding diversity in the games industry. The book begins with a deep dive into research literature and the history of diversity in the games industry to provide context around what diversity is and why it is a topic worth considering. The book looks at the different facets of diversity and games, exploring the issues and solutions within game development, studio management, event planning, and more. It provides people with practical advice about being a marginalized person in the games industry and how to be heard, how studios can support inclusive practices, and events can actively become more accessible to a diverse audience. Key Features • Explores the history of diversity in games • Provides important information around what it is like to be a marginalized person in the industry • Gives practical steps to improve the inclusivity of the industry that are designed to aid in contextualizing and upskilling new developers Author Bios Alayna Cole is the managing director of Queerly Represent Me, a not-for-profit championing queer representation in games. Alayna is also a producer at Sledgehammer Games, co-chair of the IGDA LGBTQ+ special interest group, and an award-winning games journalist and game developer. She was featured on the 2016 and 2017 Develop Pacific 30 Under 30 lists and the 2017 and 2019 Develop Pacific Women in Games lists, and she has received several other accolades in the industry. Jessica Zammit started writing in 2013 for Start Select Media, and for the next five years she followed her interest in writing about representations of mental health, diversity, and particularly, sexuality in video games. Jessica has been speaking about diversity in games at conventions such as PAX Australia since 2016 and has been featured on several other discussions in and around the topic of representation in games and games criticism. Along with her co-author, she is co-chair of the IGDA LGBTQ+ special interest group, and she was featured on the 2018 Develop Pacific 30 Under 30 and Women in Games lists.
Keywords: Computers / Programming / Games; Irina

#TimesUp on Individual Litigation Reform: Combatting Sexual Harassment through Employee-Driven Action and Private Regulation - Dugan, Natalie (Columbia Journal of Law and Social Problems, 2020)
Keywords: Bibliographie; Irina; Nettoyer

Experiencing Male Dominance in Swedish Film Production - Jansson, Maria; Wallenberg, Louise (Women in the International Film Industry: Policy, Practice and Power, 2020)
Sweden has been hailed for its recent success in increasing the number of female directors, scriptwriters and producers. Published reports, panel discussions and a vast number of press conferences on the pressing matter of gender equality within the industry together with a 5050 quota have all put the Swedish film industry—and its CEO Anna Serner—on the map. However, the last couple of years has disclosed several scandals regarding sexism and discrimination in the Swedish film industry—just as in other national film industries. This paper sets out to discuss how female film workers (e.g., directors, actors and producers) understand and negotiate their experiences of male dominance within their work context. Based on a series of interviews with women working in Swedish film from the early 1960s until today, we analyze similarities and differences in experiences as well as how these experiences are explained by the interviewees. Their stories are analyzed by using feminist institutional theory to understand how policy, funding schemes and other institutional aspects are intertwined with their experiences. The paper sets out to analyze three themes: (1) comments and suggestions during production and post-production regarding female protagonists; (2) experience of gender trouble in the process of fundraising; and (3) strategies used by the interviewed filmmakers to produce a more women-friendly environment during productions.
Keywords: Irina

Gender Equality in British Film-making: Research, Targets, Change - Cobb, Shelley; Williams, Linda Ruth (Women in the International Film Industry: Policy, Practice and Power, 2020)
In October 2017, the British Film Institute declared that it would commit to specific targets for gender equality and diversity in key production roles on films with support from the Film Fund. This decision by the BFI to set targets, arguably, did not come just from their own diversity and inclusion goals. Activist film-makers had previously called for targets for the Film Fund, especially for women directors. This chapter will give an accounting of the current state of gender (in)equality in the UK industry by: outlining new research that has clarified the stagnant inequality in the UK film industry; articulating the key role of a network of activist groups (that include researchers, professional and campaigning bodies, exhibitors and film-makers) to bring attention to the problem; putting pressure on the film industry and public bodies; and summarising institutional responses to that pressure since 2016, with a critical analysis of the potential and limits of the BFI’s relatively recently implemented diversity and equality targets.
Keywords: Bibliographie; Irina; Nettoyer